Assessing the Causes Behind the Late Quaternary Extinction of Horses in South America Using Species Distribution Models - Villavicencio, Natalia A.; Corcoran, Derek; Marquet, Pablo A. (Frontiers in Ecology and Evolution, 2019)
At the end of the Pleistocene, South America witnessed the loss of an 83% of all megafaunal genera that inhabited the continent at that time. Among the taxa that disappeared were all the representatives of the Equidae family, including several species of Equus and Hippidion. Previous studies have investigated the causes behind the extinction of horses in South America using radiocarbon data sets to set the time of extinction and compare it to the timing of major climate changes and human arrival. While these studies have shown to be informative, they are available only for some regions of the continent. In the present work we use Paleo Species Distribution Models to estimate the potential distribution of Equus neogeus, Hippidion saldiasi, Hippidion devillei and Hippidion principale in South America from the Last Glacial Maximum (LGM) through the early Holocene. The main goal is to track changes in the potential area of distribution for these taxa as they approached to the time of their extinction between 12-10 kyr BP, to test the role of climate changes in the process of extinction. The distribution models show the Pampas, El Chaco and Central Chile as major areas of distribution for E. neogeus and H. principale during the LGM. The high Andes and central Argentina appear as potential area for H. devillei and southern South America as a potential area of distribution for H. saldiasi during the LGM. A major contraction of the potential areas of distribution is observed towards the beginning of the Holocene for all species of horses, occurring along with a shift of these areas towards higher latitudes and higher altitudes. The moments of major changes in the potential areas of distribution happened at times when humans were present in most of the different areas of South America. Even if a reduction in the potential area of distribution is not probe for a main role of environmental changes in driving the demise of horses, the models presented here suggest an increased risk of extinction for these taxa during the late Pleistocene which was accompanied by a spread of humans in the continent.